2017
DOI: 10.4209/aaqr.2017.01.0045
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Catalytic Oxidation of Gaseous Toluene over MnO2-Based Ozone Decomposition Catalysts Immobilized on a Nonwoven Fabric

Abstract: Degradation of toluene gas by ozone catalytic oxidation (OZCO) by using a MnO 2 -based ozone decomposition catalyst (ODC) was investigated to clarify the reactive site of ODC material with O 3 . An optimum structure for the ODC to remove O 3 and toluene were proposed. For honeycomb ODC, toluene degradation by OZCO occurred only around the entrance of the honeycomb ODC, and we expected that a thinner ODC would increase the toluene degradation efficiency. A nonwoven fabric on which ODC was immobilized was develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Among many catalysts, MnO 2 ‐based materials have been extensively studied in the catalyst degradation of VOCs due to their natural abundance, environmentally friendliness, low cost, and specific chemical/physical properties, including different crystal structures and suitable redox activity. Currently, the reported types of VOCs degraded by MnO 2 ‐based materials include benzene series (such as toluene, [ 166,217,226,430–438 ] benzene, [ 171,173,439–441 ] ethylbenzene, [ 442–444 ] and o ‐xylene [ 297,445–448 ] ), formaldehyde, [ 54,86,116,123,137,155,156,296,449–455 ] propane, [ 456 ] aerobic sulfide, [ 172 ] methyl mercaptan, [ 299,457 ] acetone, [ 458,459 ] etc. Among them, formaldehyde and benzene series are the most common VOC pollutants in the air that have been studied the most ( Table 3 ).…”
Section: Environmental Applicationsmentioning
confidence: 99%
“…Among many catalysts, MnO 2 ‐based materials have been extensively studied in the catalyst degradation of VOCs due to their natural abundance, environmentally friendliness, low cost, and specific chemical/physical properties, including different crystal structures and suitable redox activity. Currently, the reported types of VOCs degraded by MnO 2 ‐based materials include benzene series (such as toluene, [ 166,217,226,430–438 ] benzene, [ 171,173,439–441 ] ethylbenzene, [ 442–444 ] and o ‐xylene [ 297,445–448 ] ), formaldehyde, [ 54,86,116,123,137,155,156,296,449–455 ] propane, [ 456 ] aerobic sulfide, [ 172 ] methyl mercaptan, [ 299,457 ] acetone, [ 458,459 ] etc. Among them, formaldehyde and benzene series are the most common VOC pollutants in the air that have been studied the most ( Table 3 ).…”
Section: Environmental Applicationsmentioning
confidence: 99%
“…Since the enhancement of the oxidation efficiency in the presence of O3 is attributable to a formation of highly reactive O atoms [29,32,33], catalytic O3 decomposition (over Mn/Al2O3 or Al2O3) as well as gas-phase decomposition (in the empty reactor) was also studied in detail. The results obtained are shown in Figure 5.…”
Section: O3 Decompositionmentioning
confidence: 99%
“…The high efficiency of supported MnO x catalysts in the OZCO of VOCs can be attributed to their ability in terms of O 3 decomposition [30]. It has been reported that highly reactive oxygen species such as atomic oxygen, peroxide, and OH radicals are formed (Equations ( 1)-( 4)) on the surface of metal oxides as a result of O 3 decomposition [30][31][32][33]. These species can completely oxidize adsorbed VOCs to CO 2 , even at room temperature (RT).…”
Section: Introductionmentioning
confidence: 99%
“…Although the active oxygen species in plasma are shortliving and unstable, they can be adsorbed by the catalyst and interact with the ion on the catalysts surface. For example, when O 3 reaches the catalysts surface, O atoms, O 2 and OH radicals are formed on the surface (Sekiguchi et al, 2017). Therefore, the ratio of O and O α /(O α + O β ) on catalysts surface prepared by plasma is relatively high.…”
Section: Characterization Of the Catalystsmentioning
confidence: 99%